Cost-effective analysis of mechanical thrombectomy alone in the treatment of acute ischaemic stroke: a Markov modelling study. Issue 4 (6th April 2022) - Han, Mingyang; Qin, Yongkai; Tong, Xin; Ji, Linjin; Zhao, Songfeng; Liu, Lang; Chen, Jigang; Liu, Aihua
Abstract : Objective: Recently, a randomised controlled trial (DIRECT-MT) demonstrated that mechanical thrombectomy (MT) was non-inferior to MT with intravenous alteplase as to the functional outcomes. This study aims to investigate whether MT alone is cost-effective compared with MT with alteplase in China. Methods: A Markov decision analytic model was built from the Chinese healthcare perspective using a lifetime horizon. Probabilities, costs and outcomes data were obtained from the DIRECT-MT trial and other most recent/comprehensive literature. Base case calculation was conducted to compare the costs and effectiveness between MT alone and MT with alteplase. One-way and probabilistic sensitivity analyses were performed to evaluate the robustness of the results. Results: MT alone had a lower cost and higher effectiveness compared with MT with alteplase. The probabilistic sensitivity analysis demonstrated that, over a lifetime horizon, MT alone had a 99.5% probability of being cost-effective under the willingness-to-pay threshold of 1× gross domestic product per capita in China based on data obtained from the DIRECT-MT trial. These results remained robust under one-way sensitivity analysis. Conclusions: MT alone was cost-effective compared with MT with alteplase in China. However, cautions are needed to extend this conclusion to regions outside of China.